Valdosta High School Scrapbook 10, September – December 1969 - Valdosta High School (My University, 1969)
This item details the 1969 football season as well as other events. One prominent event was a walkout staged by the students involving civil rights.
This item contains 1 PDF with 157 pages and a title page
Keywords: Newspapers; Photographs; Scrapbooks; Lowndes County (Ga.); American Football